| x^2 -2x+4|=2x+1 x^3-x=0 2x^2+3x=0 |2x-4|=3(1-x)

Question

| x^2 -2x+4|=2x+1
x^3-x=0
2x^2+3x=0
|2x-4|=3(1-x)

in progress 0
Kaylee 2 tháng 2021-07-25T22:08:08+00:00 2 Answers 3 views 0

Answers ( )

    0
    2021-07-25T22:09:26+00:00

    |x²-2x+4|=2x+1

    TH1: x²-2x+4=2x+1 (x≥2)

    ⇔ x²-2x+4-2x-1=0

    ⇔ x²-4x+3=0

    ⇔ x²-x-3x+3=0

    ⇔ x(x-1)-3(x-1)=0

    ⇔ (x-1)(x-3)=0

    ⇔ x=1(KTM) và x=3(TM)

    TH2: -(x²-2x+4)=2x+1 (x<2)

    ⇔ -x²+2x-4-2x-1=0

    ⇔-x²-5=0

    ⇔ -x²=5

    ⇔ x²=-5⇒ vô lí

    x³-x=0

    ⇔x(x²-1)=0

    ⇔x(x-1)(x+1)=0

    ⇔x=0 x=1 x=-1

    2x²+3x=0

    ⇔x(2x+3)=0

    ⇔x=0 và x=-3/2

    |2x-4|=3(1-x)

    ⇔TH1:

    2x-4=3(1-x)  (x≥2)

    2x-4=3-3x

    ⇔2x+3x=3+4

    ⇔5x=7

    ⇔x=7/5(KTM)

    TH2 -2x+4=3(1-x)    (x<2)

    ⇔-2x+4=3-3x

    ⇔-2x+3x=3-4

    ⇔x=-1(TM)

    0
    2021-07-25T22:10:01+00:00

    Đáp án + Giải thích các bước giải:

    `|x^{2}-2x+4|=2x+1   (1)`

    Xét : `x^{2}-2x+4=(x-1)^{2}+3≥3  ∀x`

    Khi đó `|x^{2}-2x+4|=x^{2}-2x+4`

    `(1)<=>x^{2}-2x+4=2x+1`

    `<=>x^{2}-2x-2x+4-1=0`

    `<=>x^{2}-4x+3=0`

    `<=>(x-2)^{2}-1=0`

    `<=>(x-2-1)(x-2+1)=0`

    `<=>(x-3)(x-1)=0`

    `<=>` \(\left[ \begin{array}{l}x-3=0\\x-1=0\end{array} \right.\) 

    `<=>` \(\left[ \begin{array}{l}x=3\\x=1\end{array} \right.\) 

    Vậy phương trình có tập nghiệm là : `S={3;1}`

    `x^{3}-x=0`

    `<=>x(x^{2}-1)=0`

    `<=>x(x-1)(x+1)=0`

    `<=>` \(\left[ \begin{array}{l}x=0\\x-1=0\\x+1=0\end{array} \right.\) 

    `<=>` \(\left[ \begin{array}{l}x=0\\x=1\\x=-1\end{array} \right.\) 

    Vậy phương trình có tập nghiệm là : `S={0;±1}`

    `2x^{2}+3x=0`

    `<=>x(2x+3)=0`

    `<=>` \(\left[ \begin{array}{l}x=0\\2x+3=0\end{array} \right.\) 

    `<=>` \(\left[ \begin{array}{l}x=0\\x=-\dfrac{3}{2}\end{array} \right.\) 

    Vậy phương trình có tập nghiệm là : `S={0;-(3)/(2)}`

    `|2x-4|=3(1-x)`

    `<=>|2x-4|=3-3x`

    `<=>` \(\left[ \begin{array}{l}2x-4=3-3x\ (ĐK:2x-4≥0)\\4-2x=3-3x\ (ĐK:2x-4<0)\end{array} \right.\) 

    `<=>` \(\left[ \begin{array}{l}2x+3x=4+3\ (ĐK:2x≥4)\\3x-2x=3-4\ (ĐK:2x<4)\end{array} \right.\) 

    `<=>` \(\left[ \begin{array}{l}5x=7\ (ĐK:x≥2)\\x=-1\ (ĐK:x<2)\end{array} \right.\) 

    `<=>` \(\left[ \begin{array}{l}x=\dfrac{7}{5}\ (KTM)\\x=-1\ (TM)\end{array} \right.\) 

    Vậy phương trình có một nghiệm là : `x=-1`

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )